Cultivation-dependent and cultivation-independent characterization of hydrocarbon-degrading bacteria in Guaymas Basin sediments - Gutierrez, Tony; Biddle, Jennifer F.; Teske, Andreas; Aitken, Michael D. (Frontiers in Microbiology, 2015)
Marine hydrocarbon-degrading bacteria perform a fundamental role in the biodegradation of crude oil and its petrochemical derivatives in coastal and open ocean environments. However, there is a paucity of knowledge on the diversity and function of these organisms in deep-sea sediment. Here we used stable-isotope probing (SIP), a valuable tool to link the phylogeny and function of targeted microbial groups, to investigate polycyclic aromatic hydrocarbon (PAH)-degrading bacteria under aerobic conditions in sediments from Guaymas Basin with uniformly labeled [13C]phenanthrene. The dominant sequences in clone libraries constructed from 13C-enriched bacterial DNA (from phenanthrene enrichments) were identified to belong to the genus Cycloclasticus. We used quantitative PCR primers targeting the 16S rRNA gene of the SIP-identified Cycloclasticus to determine their abundance in sediment incubations amended with unlabeled phenanthrene and showed substantial increases in gene abundance during the experiments. We also isolated a strain, BG-2, representing the SIP-identified Cycloclasticus sequence (99.9% 16S rRNA gene sequence identity), and used this strain to provide direct evidence of phenanthrene degradation and mineralization. In addition, we isolated Halomonas, Thalassospira and Lutibacterium spp. with demonstrable phenanthrene-degrading capacity from Guaymas Basin sediment. This study demonstrates the value of coupling SIP with cultivation methods to identify and expand on the known diversity of PAH-degrading bacteria in the deep-sea.